Social stress effects on pigmentation and monoamines in Arctic charr - Backstrom, Tobias; Heynen, Martina; Brannas, Eva; Nilsson, Jan; Winberg, Svante; Magnhagen, Carin (Elsevier B.V., 2015)
Pigmentation often signals status and in general melanin-based pigmentation is indicative of aggression and stress resilience in vertebrates. This is evident in the salmonids Atlantic salmon (Salmo salar) and rainbow trout (Oncorhynchus mykiss) where more melanin spotted individuals are more stress resilient. However, in the salmonid Arctic charr (Salvelinus alpinus) it seems as if it is carotenoid-based pigmentation that signals aggression and stress resilience. In our study, social stress effects on carotenoid-based spots, and behavioural and physiological stress responses were investigated. Socially stressed individuals have more spots, and behavioural stress responses were associated with spots. Some of the results concerning physiological stress responses, such as plasma cortisol levels and monoaminergic activity, are associated with spottiness. Further, the earlier proposed lateralization of spots, with left side connected to stress responsiveness and right side to aggression, is to some extent validated although not conclusively. In conclusion, this study provides further evidence that more stressed charr have more carotenoid spots, and for the first time monoaminergic activity is shown to be connected with carotenoid pigmentation. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Aggression; Carotenoid pigmentation; Lateralization; Monoamine; Salmonid; Social stress